2023
DOI: 10.3390/microorganisms11030549
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Pseudomonas plecoglossicida 2,4-D and Humic Substances on the Growth, Pigment Indices and Concentration of Hormones in Wheat Seedlings Grown under Water Deficit

Abstract: The search for ways to increase plant productivity in drought conditions is of fundamental importance, since soil moisture deficiency is widespread and leads to critical crop losses. The aim of this study was to identify the effects of plant growth-promoting bacteria and humic substances on the growth, chlorophyll, flavonoids, nitrogen balance index, and concentration of cytokinins and abscisic acids in wheat plants grown in the laboratory under conditions of water deficit. An increase in the accumulation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…In wheat, the amount of ABA is often negatively correlated with photosynthesis efficiency and leaf Chl content [86]. The observed increase in Chl concentration in wheat plants treated with P. plecoglossicida 2,4-D was found to be correlated with a decrease in ABA concentration in plant shoots during water deficit [96]. Similar results were obtained in our study, where BS-treated wheat plants showed comparable outcomes under osmotic stress (Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In wheat, the amount of ABA is often negatively correlated with photosynthesis efficiency and leaf Chl content [86]. The observed increase in Chl concentration in wheat plants treated with P. plecoglossicida 2,4-D was found to be correlated with a decrease in ABA concentration in plant shoots during water deficit [96]. Similar results were obtained in our study, where BS-treated wheat plants showed comparable outcomes under osmotic stress (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…The increased accumulation of Chl in PGPB-treated and stressed plants is likely attributed not only to the hormonal effect on Chl metabolism but also to an increase in root biomass. This improvement in root biomass enhances the roots' ability to absorb nitrogen, which is essential for Chl synthesis [22,96]. So, plant colonization with PGPB can activate multiple mechanisms that assist plants in coping with stress conditions, including maintaining photosynthesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…The additive influence of humates and bacteria on cultivated plants may be due to the effect of humates on bacterial growth. We have recently shown that humates increase bacterial abundance in the rhizosphere of wheat [ 27 ]. A recent review highlighted the lack of information on the impact of humates on the composition and function of soil microbial communities [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains Pseudomonas protegens DA1.2 and Pseudomonas sp. 4CH [ 9 ] were selected from a collection of microorganisms (Ufa Institute of Biology, Ufa, Russia), since their combination with humates was previously shown to stimulate the growth of wheat plants [ 27 ]. Pseudomonas protegens DA1.2 synthesizes indolylacetic acid, promotes the mobilization of phosphorus from insoluble compounds, fixes atmospheric nitrogen, and exhibits antagonism to microscopic fungi [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hormones were immunoassayed with appropriate specific antibodies. Enzyme Linked Immunosorbent Assay (ELISA) was performed according to competitive protocol [ 16 , 17 ]. In short, conjugate of hormone and ovalbumin dissolved in phosphate buffer was adsorbed onto the walls of microplate wells.…”
Section: Methodsmentioning
confidence: 99%